Suitable Recruitment Strategy to Increase the Quality and the Quantity of TransPerfect’s Digital Specialist - Nikita Luisa (iBuss Management, 2022)
Human resource management is known as one of the key successes why business in international scope could go bigger in the world. As quoted from Steve Jobs, “The secret of my success is that we have gone to exceptional lengths to hire the best people in the world.”, we cannot deny the importance of having the right recruitment strategy in a company to gather the best talent and quality to enhance company’s growth. This goes the same for TransPerfect, an international translation company who has grown rapidly and hit 1$ billion revenue last year. Since the company provides translation services, they work closely with digital specialists, and hence, this is one of the key factors regarding their success and growth up until today. However, challenges are inevitable to face, especially for big company like TransPerfect. This report would give a suitable recruitment strategy to increase the quality and the quantity of TransPerfect’s current manpower, which is called digital specialists. Not only that this report would help the company to identify how they could reach out those potential new hirers, the report will also give them more analysis towards their current weaknesses and challenges to tackle.Keywords: Human resource management, Vendor management, TransPerfect, Recruitment strategy